UNILATERAL POSTERIOR CROSS-BITE IN PRIMARY DENTITION- CASE REPORT - Andreea Simona Pop; Alexandrina Muntean; Paula Jiman; Dan Buhățel; Anca Ionel; Claudia Nicoleta Feurdean; Willi Andrei Uriciuc; Roxana Ioana Bordea; Arin Ioan Sava; Adela Cristina Lazăr; Aranka Ilea (Romanian Journal of Oral Rehabilitation, 2022)
Aim of the study Preventive orthodontic care necessitates rational treatment planning among children even in an early stage of dental and skeletal development. Material and methods The oral rehabilitation of patients with unilateral posterior crossbite in primary dentition remains a challenge, for the clinician and for the patient, due to functional, aesthetic and self-maintenance alterations, and requires early orthodontic treatment. To illustrate the treatment difficulties of such a pathology, we present a clinical case, a five years old girl diagnosed with unilateral posterior cross- bite, narrow maxilla and left mandibular shift. Results In order to fulfil the therapeutic objectives, a rapid palatal expander with a median screw welding on band cemented on 5.5, 6.5 was applied. After 3 month the transversal unilateral discrepancy was corrected, with stable occlusal contacts. Conclusions For skeletal transverse problems the appliance of choice is a rapid maxillary expander especially for growing patients.